Miller's anesthesia - Miller, Ronald D., 1939- (Elsevier/Saunders, 2015)
From fundamental principles to advanced subspecialty procedures, Miller's Anesthesia covers the full scope of contemporary anesthesia practice. This go-to medical reference book offers masterful guidance on the technical, scientific, and clinical challenges you face each day, in addition to providing the most up-to-date information available for effective board preparation.